Maternal Mortality in Klaten Regency (Determinant Factors Analysis) - Sesunan, Arfan Syahfani; Respati, Supriyadi Hari; Sulistyowati, Sri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Failure in reducing maternal mor